Effects on white blood cell counts and the NLRP3 inflammasome due to dust and cobalt exposure in the hard metal industry. (2nd January 2022) - Hedbrant, Alexander; Eklund, Daniel; Andersson, Lena; Bryngelsson, Ing-Liss; Persson, Alexander; Westberg, Håkan; Särndahl, Eva
Abstract: Introduction: In light of potential negative health effects of cobalt exposure, a characterization of inflammatory mechanisms in exposed individuals is warranted. The current study investigated cobalt exposure in the Swedish hard metal industry and its relationship to inflammatory markers, including NLRP3 inflammasome activation and white blood cell (WBC) counts. Materials and methods: Inhalable cobalt and dust exposures, and systemic cobalt levels, were determined for 72 workers in the hard metal industry and linear regression models were applied to correlate exposure to markers of inflammasome activation and WBC counts. Results: Mean exposures to inhalable dust (0.11 mg/m 3 ) and cobalt (0.0034 mg/m 3 ) were below the Swedish occupational exposure limits, and these low exposures did not correlate with any investigated outcomes. Instead, cobalt blood levels significantly correlated with a ca 10% decrease in IL-18 plasma levels per 10 nM cobalt increase. Furthermore, pre-shift cobalt blood and/or urine levels significantly correlated with some WBC measures, including decreased neutrophil-to-lymphocyte ratio, increased lymphocyte-to-monocyte ratio, and lymphocyte counts. Conclusion: The low inhalable particle exposures had no impact on WBC counts and inflammasome activation. Instead, systemic cobalt levels, which also include skin exposure, demonstrated possible suppressive effects on inflammatory responses in cobalt-exposed individuals in the hard metal industry.